Epidemiological and clinicopathological studies based on web registration system (J-RBR/J-KDR) - Yokoyama, Hitoshi (Japanese journal of pediatric nephrology, 2014)
Since 2007, Japanese Society of Nephrology (JSN) started the registration of renal biopsy cases, i.e. Japan Renal Biopsy Registry/J-RBR, which was constructed on the web page of University Hospital Medical Information Network (UMIN) Center. Based on J-RBR experience, JSN reorganized the system including 130 centers and expanded the registration to not only renal biopsied subjects, but also non-renal biopsied refractory renal disease subjects, such as nephrotic syndrome, rapidly progressive glomerulonephritis (RPGN), polycystic kidney diseases (PKD), pediatric kidney disease, and chronic kidney disease, as Japan Kidney Disease Registry/J-KDR. The registered cases were 21,483 at the end of May 2013. The clinical and pathological diagnoses, and clinical data were analyzed every term. In addition, the epidemiological and clinicopathological prospective studies based on J-RBR/J-KDR data of nephrotic syndrome, RPGN, IgA nephropathy, PKD and diabetic nephropathy were promoted to make the qualified clinical evidence of Japanese renal diseases, and to prevent these refractory and chronic kidney diseases in the future.